Jenayah komputer: perbandingan menurut Akta Jenayah Komputer 1997 dan prinsip undang-undang jenayah Islam - Nazura Abdul Manap,; Jasri Jamal, (Fakulti Undang - Undang, 2003)

(untitled)
Cyber space offers some new and highly sophisticated opportunities for criminal misconduct and they create potential to commit traditional crimes in a modern way. The nature of criminal behaviour which requires phisycal act then, has turn into a crime which only relies on a click of mouse or a touch of keyboard. The provisions in criminal statute should develop to cater the difference in nature in cyber-crime related law of the Computer Crime Act 1997 in order to restrain the cyber crimes activities. The aim of this paper is to highlight the offences stipulated in the Computer Crime Act 1997 as well as to compare the provisions with Islamic-principles. To what extent the Islamic criminal provisions is applicable, which based on Al Quran and Al Sunnah, in solving problems related to virtual crimes